Evidence for the Keplerian Orbit of a Close Companion Around a Giant Star - El Mellah, I (NATURE PORTFOLIO, 2026)
Close companions influence stellar evolution through tidal interactions, mass transfer and mass-loss effects. While such companions are detected around young stellar objects, main-sequence stars, red giants and compact objects, direct observational evidence of close-in companions around asymptotic giant branch (AGB) stars has remained elusive. Here we present (sub)millimetre time-domain imaging spectroscopy revealing the Keplerian motion of a close-in companion around the AGB star pi 1 Gruis. The companion, slightly more massive than the AGB star, is likely a main-sequence star. Unlike more evolved stars with companions at comparable distances, the companion of pi 1 Gruis follows a circular orbit, suggesting an eccentricity-generating mechanism during the late- or post-AGB phase. Our analysis suggests that model-predicted circularization rates may be underestimated. Our results highlight the potential of multi-epoch (sub)millimetre interferometry in detecting the Keplerian motion of close companions to giant stars and open avenues for our understanding of tidal interaction physics and binary evolution.